Neuronal Spleen tyrosine kinase (SYK) mediates cytokine release in Transgenic Tau P301S mice organotypic brain slice cultures. (11th June 2020) - Schweig, Jonas Elias; Yao, Hailan; Jin, Chao; Crawford, Fiona; Mullan, Michael; Paris, Daniel
Highlights: SYK is mainly expressed in neurons within the CNS. In Tg Tau P301S mice SYK activation occurs in neurons but not in glia. SYK inhibition reverses LPS effects on cytokine release ex vivo in the brain. SYK is a key regulator of the neuroinflammation induced by tau pathology. Abstract: The Spleen Tyrosine Kinase (SYK) is known for its involvement in B-cell and T-cell signaling, modulating the peripheral immune response. We have previously shown that SYK is overactive in the brains of human Alzheimer's Disease (AD) patients, as well as mouse models of AD and tauopathy including Tg Tau P301S mice. More specifically, SYK activation occurs mainly in neurons in human AD brain specimens and mouse models of AD and colocalizes with tau pathogenic species, suggesting it could play a role in AD pathobiology. To assess the possible contribution of SYK to the inflammatory response induced by tau pathology, we analyzed cytokine production in organotypic brain slices cultures from Tg Tau P301S mice and wild-type littermates. Organotypic brains slices from Tau P301S mice produce more cytokines than brain slices from wild-type littermates while SYK inhibition completely antagonizes cytokine production from Tg Tau P301S brain slices. Interestingly, LPS exacerbates the production of pro-inflammatory cytokines in Tg Tau P301S brain sections compared to wild-type organotypic sections while SYK inhibition alleviates the release of pro-inflammatory cytokines induced by LPS. Given that SYK is mainly activated in neurons in Tg Tau P301S mice and not in glial cells, these data suggest that neuronal SYK contributes to the neuroinflammation triggered by the tau pathology. SYK represents an attractive target for regulating the underlying neuroinflammatory component induced by tau pathology.